Sunday

March 1, 2015

March 1, 2015

Posted by **vero** on Wednesday, January 7, 2009 at 5:01pm.

-5x-4y=-11

10x=-6-y

help me plz......

- Math ....urgent help -
**DrBob222**, Wednesday, January 7, 2009 at 5:32pmPick any number that will multiply by one of the equations to give the same number as in the other equation. For example, if we multiply equation 1 by 2 we would have

-10x-8y=-22. Why did I pick 2 as a multiplier. Because it gives me -10x and 10x agrees with the x in equation 2 (the sign is different but that's ok). Then adding equation 1 to equation 2 will eliminate x because -10x+10x = 0x. OK?

- Math ....urgent help -
**Damon**, Wednesday, January 7, 2009 at 5:54pm-5x-4y=-11

10x=-6-y

line them up - something*x + something*y = something

-5 x - 4 y = -11

10 x + 1 y = -6

we could now multiply the first equation by 2 to make the absolute value of the x coefficient 10 for both -then eliminate x by adding them

or

we could multiply the second by 4 to make the absolute value of the y coefficient 4 for both. then eliminate y by subracting them.

Lets do the second and eliminate y:

-5 x - 4 y = -11

40 x + 4 y = -24

------------------ now add

+35 x +0 y = -35

so

x = 35/35 = -1 now go back and use either equation to find y

y = -10(-1) -6

y = 4

- Math ....urgent help -
**Anonymous**, Wednesday, January 7, 2009 at 6:00pmoo......thanks to both of you so much

- Math ....urgent help -
**peacemaker**, Monday, April 16, 2012 at 4:13amiwnt hlp wth reduction formulas

- Math ....urgent help -
**Chelle**, Wednesday, January 8, 2014 at 9:16pm-5x - 4y = -11

10x = -6 - y

For the second equation, move -y to the left side and change sign to positive.

-5x - 4y = -11

10x + y = -6

Now you are either going to eliminate the x's or y's first.

If it is x's, then multiply the first equation by 2.

If it is y's, then multiply the second equation by 4.

I'll PICK THE SECOND EQUATION

4(10x + y) = 4(-6)

40x + 4y = -24

-5x - 4y = -11

40x + 4y = -24

_______________________

35x = -35 > divide by 35 on both sides

x = -1

Now solve for y by plugging in x value in either equation.

-5(-1) -4y = -11

5 - 4y = -11

-5 -5

______________________

-4y = -16 > divide by -4 on both sides.

y = 4

**Answer this Question**

**Related Questions**

LIVING ENVIRONMENT - the ability to grow in size is a characteristic of living ...

Math help plz ASAP. - Rationalize each denominator. 6 + square root of 2 ...

I NEED HELP!!:(!!!! HELP ME PLZ!! - I GOT A FEW QUESTIONS SO what is a cell part...

biology - a boy inherits genes for tallness,but his growth is limited as a ...

math - the volume of a rectangular solid is given by expressions given below.in...

math - the volume of a rectangular solid is given by expressions given below.in...

Math - Plz cud sombdy show me long division method of x^4/(x-1)(x^2+1)???? Plz ...

Math - Plz cud sombdy show me long division method of x^4/(x-1)(x^2+1)???? Plz ...

Math - Plz cud sombdy show me long division method of x^4/(x-1)(x^2+1)???? Plz ...

physics(URGENT!!!!!) - EDXers!!! Plz help with MITx 8.01x I don't know how to ...